Optimize Energy Efficiency Through Base Station Switching and Resource Allocation For 5g Heterogeneous Networks - Tiwari, Amit Kumar; Mishra, Pavan Kumar; Pandey, Sudhakar (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Energy and spectrum are the crucial factors on which future heterogeneous networks maintain green and sustainable development depends. Optimization of spectrum and power is the need of the day. The proposed algorithm uses Base Station (BS) switching model for the power optimization in which BS is made to sleep/ awake based on the user density and precursory observed data. With this dynamic control of the power of BS, a considerable power saving is observed. Spectrum optimization is attained using spectrum slicing, in which, initially, the traffic modeling is done considering user density, demand, and other parameters. Then the data assembled is deeply analyzed, and then Hidden Markov Model is used to allocate the spectrum based on the initial processing. This technique helps in the effective distribution of spectrum, and the spectrum can be appropriately utilized among the users belonging to different density groups having varied applications. The paper aims to increase spectral efficiency and power optimization with improvement in the Quality of Service (QoS) in addition to the user’s quality of Experience (QoE).